2016
DOI: 10.1002/adma.201600784
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Perovskite‐Quantum‐Dot Light‐Emitting Diodes by Surface Engineering

Abstract: A two-step ligand-exchange strategy is developed, in which the long-carbon- chain ligands on all-inorganic perovskite (CsPbX , X = Br, Cl) quantum dots (QDs) are replaced with halide-ion-pair ligands. Green and blue light-emitting diodes made from the halide-ion-pair-capped quantum dots exhibit high external quantum efficiencies compared with the untreated QDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
1,095
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 983 publications
(1,117 citation statements)
references
References 54 publications
17
1,095
1
4
Order By: Relevance
“…These results indicated that the composites are consisted of perovskite QDs and anthracene crystals. 3 …”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the composites are consisted of perovskite QDs and anthracene crystals. 3 …”
Section: Resultsmentioning
confidence: 99%
“…Recently, Pan et al utilized a ligand-exchange method to replace the long ligands with shorter ligands to enhance the performances of perovskite NC-LEDs greatly. 28 Moreover, Yassitepe et al proposed a strategy that utilized tetraoctylammonium halides to prepare CsPbX 3 NCs, eliminating the use of oleylamine and enhancing the colloidal stability of the solution. 23 Inspired by the solution-phase ligand exchange in chalcogenide quantum dots, 29 we tried to use a mixture of oleylamine/DDAB to modify the surface passivation of NCs.…”
Section: Introductionmentioning
confidence: 99%
“…Originally, perovskites of the generic formula, CH 3 NH 3 PbX 3 (X=I, Br, Cl), have been utilized to replace conventional sensitizers in dye-sensitized solar cells (DSSCs) where they were used for absorbing the sun light spectrum. [5][6][7][8] However, soon after it has been realized that perovskites are characterized by good electronic and optoelectronic properties, [9][10][11][12][13][14][15][16] that can be exploited for advancing thin-film and low-dimensional [17][18][19][20][21] versions of solar cells, as well as for developing perovskite-based light emitting diodes (LEDs) [22][23][24] and lasers. [25][26][27][28][29][30] The rapid progress in the field of perovskites has also raised certain questions concerning fundamental properties of these materials, particularly about phenomena associated with lowdimensional effects and size-dependent properties of perovskite nanostructures.…”
Section: Introductionmentioning
confidence: 99%